The Investıgatıon Of The Posıtıonal Changes Of The Lower Fırst Permanent Molars Durıng The Perıod Of Transıtıon From Mıxed To Permanent Dentıtıon - Abdulvahit Erdem (Galenos Yayinevi, 1990)
This study has been planned to investigate the sagittal and horizontal positional changes of the lower permanent first molars, which are physiologically seen during the transition period from mixed to permanent dentition. For this purpose, the orthodontic models and the cephalometric head films of twenty students, eight girls and twelve boys, taken in the mixed and the permanent dentition period were chosen from the files of our department. The measurements from the first and second records were compared. In conclusion, it was found that lower first permanent molars displaced both sagittally and horizontally in the permanent dentition with respect to mixed dentition.